Technology and equipment for friction stir preweld edge preparation - Y. G. Lyudmirsky; А. N. Soloviev; М. V. Soltovets; R. R. Kotlyshev; I. V. Mironov; А. V. Kramskoy (Advanced Engineering Research, 2021)
Introduction. Friction stir welding is widely used due to certain advantages of this method. Factors that reduce the strength of joints made of high-strength aluminum alloys are considered. When welding flat sheets, an effective way to increase the strength of the weld is edge thickening. The paper proposes a method for such thickening. A device is developed, calculations and experiments are carried out. Materials and Methods. Laboratory equipment has been developed to provide simultaneous thickening of two edges to be welded. The main component of this equipment is a steel roller, which is rolled along the edges of two blanks and thickens them due to plastic deformation. The same setup can be used for the friction stir welding process. To calculate the geometry of the thickened edges and the parameters of the deforming roller depending on the value of the edge settlement, a mathematical model based on the contact problem for elastic (roller) and elastoplastic (blank) bodies with a bilinear hardening law has been developed. A three-dimensional simplified geometric model of the facility with account of its symmetry has been constructed. On the contact surfaces, special contact finite elements were selected and the finite element mesh was refined. The numerical implementation of the model was carried out in the ANSYS package. Results. The theoretical model provides assessing the stress-strain state of interacting elements. On the basis of the developed finite element model, the parameters of the thickened edges are calculated, and the geometry of the thickened edges is defined. Using the developed laboratory equipment, full-scale experiments on thickening the edges of the blanks were carried out. The experimental results confirm the adequacy of the developed theoretical model and calculations based on it. The possibility of adjusting the size of the thickened edges is shown.Discussion and Conclusion. A technology for obtaining thickened edges in places of welds is proposed. It will reduce the metal consumption of structures and ensure the bearing capacity of welded joints not lower than similar characteristics of the base metal. A theoretical model of the process is developed, and a numerical experiment providing the selection of the process parameters is carried out.